Memory T cells possess an innate-like function in local protection from mucosal infection - Tanvi Arkatkar; Veronica Davé; Irene Cruz Talavera; Jessica B. Graham; Jessica L. Swarts; Sean M. Hughes; Timothy A. Bell; Pablo Hock; Joe Farrington; Ginger D. Shaw; Anna Kirby; Michael Fialkow; et al. (The Journal of Clinical Investigation, 2023)
Mucosal infections pose a significant global health burden. Antigen-specific tissue-resident T cells are critical to maintaining barrier immunity. Previous studies in the context of systemic infection suggest that memory CD8+ T cells may also provide innate-like protection against antigenically unrelated pathogens independent of T cell receptor engagement. Whether bystander T cell activation is also an important defense mechanism in the mucosa is poorly understood. Here, we investigated whether innate-like memory CD8+ T cells could protect against a model mucosal virus infection, herpes simplex virus 2 (HSV-2). We found that immunization with an irrelevant antigen delayed disease progression from lethal HSV-2 challenge, suggesting that memory CD8+ T cells may mediate protection despite the lack of antigen specificity. Upon HSV-2 infection, we observed an early infiltration, rather than substantial local proliferation, of antigen-nonspecific CD8+ T cells, which became bystander-activated only within the infected mucosal tissue. Critically, we show that bystander-activated CD8+ T cells are sufficient to reduce early viral burden after HSV-2 infection. Finally, local cytokine cues within the tissue microenvironment after infection were sufficient for bystander activation of mucosal tissue memory CD8+ T cells from mice and humans. Altogether, our findings suggest that local bystander activation of CD8+ memory T cells contributes a fast and effective innate-like response to infection in mucosal tissue.